Epigenetic Alterations in Pancreatic Cancer - Jiaqi Shi (Pancreas, 2025)
Pancreatic cancer is the fourth leading cause of cancer death and is predicted to be the second leading cause in a decade in the US. Despite more than 50 years of research and therapeutic development, pancreatic cancer still has a median survival rate of 6 months and a 5-year overall survival around 5%. Therefore, there is an urgent need to better understand the mechanism of pancreatic cancer development, as well as to discover new biomarkers for early diagnosis, prognosis, and therapeutic targets.